Efficacy of OTC analgesics. (19th November 2012) - Moore, R. A.; Derry, C.
Summary: For many 'over‐the‐counter' (OTC) analgesics, there is little information available about their relative efficacy. We have examined information available in a series of Cochrane reviews of single doses of analgesic drugs in acute pain and migraine for its relevance for analgesic products commonly available without prescription, at doses generally equivalent to two tablets. Pain following third molar extraction was used as a homogeneous acute pain model; with the outcome of at least 50% maximum pain relief over 6 h. For many OTC drugs, there was no information available. For some OTC drugs, there was at least some information available either for the marketed product itself, or from studies that used the same doses of drug or drugs. For acute pain, data from third molar extraction studies showed that several OTC products were highly efficacious, principally non‐steroidal anti‐inflammatory drugs (ibuprofen, naproxen, diclofenac) and combination products based on ibuprofen; aspirin and paracetamol‐based products were less efficacious. Fixed‐dose combinations, especially those with ibuprofen, provided high levels of analgesia. For migraine headache, the outcome used was pain initially moderate or severe becoming no worse than mild pain (no pain, mild pain) at 2 h. Single‐dose ibuprofen 400 mg was better than aspirin and paracetamol.